Analisis Strategi Pemasaran Politik Kampanye Kukuh Haryanto Sebagai Calon Legislatif DPRD Kabupaten Wonogiri Dalam Kontestasi Pemilihan Umum Tahun 2024 - Shildamullah Danendra Mukti Ardana; Titin Purwaningsih (Jurnal Ilmu Sosial dan Ilmu Politik)
The 2024 general election stands out as one of the most dynamic elections compared to previous ones. This election was marked not only by the drama surrounding presidential and vice-presidential candidates but also by political maneuvers and the creative campaign strategies of legislative candidates from various political parties. Kukuh Haryanto, a street artist known as a street musician or "pengamen," managed to compete with other legislative candidates and secured the highest number of votes within his party in the 1st electoral district of Wonogiri Regency. This achievement was quite surprising given that his campaign was primarily conducted through social media with limited resources. This study aims to analyze in-depth the political marketing strategy employed by Kukuh Haryanto. The research adopts a qualitative method, with primary data collected through direct interviews with informants and secondary data sourced from the internet, mass media, journal articles, and previous studies relevant to the topic. Data analysis was carried out using the Internet of Things approach and Adman Nursal’s political marketing theory in a descriptive manner. The results reveal that Kukuh Haryanto has had a longstanding interest in politics. In the 2024 election, he ran as a legislative candidate using a campaign strategy centered on singing his own songs, which successfully captured public attention. However, he failed to win a legislative seat due to the intense competition and the party's insufficient vote share.